Physical mapping of herpes simplex virus-induced polypeptides. - Marsden, H S (1978)
Analysis of the polypeptides induced by 29 herpes simplex virus type 1/type 2 intertypic recombinants and correlation of the data with the crossover points in the recombinant DNAs have enabled the map positions of many polypeptides to be deduced. These include 25 polypeptides which label with [35S]methionine, 11 which label with [32P]orthophosphate, and 4 which label with [14C]glucosamine. Together with the data of Preston et al. (J. Virol., in press) on the mapping of five immediate-early polypeptides, the results show that representatives of four groups of proteins--immediate-early, late, phosphorylated, and glycosylated--map in both long and short regions. The functional organization of the herpes simplex virus genome does not therefore restrict any of these four groups to either the long or the short region.